Feasibility Study of Summer SPEAK! project of AIESEC Praha - Babica, Martin; Potluka, Oto, 1973-; Fanta, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
The purpose of this thesis is to find out whether the Summer SPEAK! project targeted on high school pupils is feasible or not. The first part of the thesis describes the organizer of Summer SPEAK! project - AIESEC Praha - and its motivation to organize the Summer SPEAK! project. What feasibility study is and how it is prepared is stated in the second part of this thesis. The third part of this thesis is the feasibility study itself, which through tools of market research, questionnaire survey, analysis of internal data of AIESEC and budgeting finds out whether Summer SPEAK! project is feasible or not. The conclusions of this thesis provide the recommendations for the Director of Cultural Projects of AIESEC Praha who will be making the go or no-go decision for Summer SPEAK! project targeted on high school pupils.
Vedoucí práce: Oto Potluka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses